2008
DOI: 10.1016/j.plaphy.2008.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shade on the development and sugar metabolism of coffee (Coffea arabica L.) fruits

Abstract: Coffee fruits grown in shade are characterized by larger bean size than those grown under full-sun conditions. The present study assessed the effects of shade on bean characteristics and sugar metabolism by analyzing tissue development, sugar contents, activities of sucrose metabolizing enzymes and expression of sucrose synthase-encoding genes in fruits of coffee (Coffea arabica L.) plants submitted to full-sun (FS) and shade (SH) conditions. Evolution of tissue fresh weights measured in fruits collected regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 46 publications
3
81
0
15
Order By: Relevance
“…Notably, also the quality of the produced bean under supra-optimal temperatures (or lower altitudes) could be affected, similarly to what was reported to C. arabica fruits, related to a faster (but incomplete) fruit maturation and to the presence of chemical detrimental compounds (as CGAs), with negative impact on the beverage quality (Vaast et al, 2006;Geromel et al, 2008;Bertrand et al, 2012;Barbosa et al, 2012). Furthermore, it is known that these environmental limitations of high temperature and chronic low water availability reported for this region will impact the plant at the physiological level, namely in what concerns the maintenance of balance between respiration and photosynthesis.…”
Section: Northeast Regionmentioning
confidence: 55%
“…Notably, also the quality of the produced bean under supra-optimal temperatures (or lower altitudes) could be affected, similarly to what was reported to C. arabica fruits, related to a faster (but incomplete) fruit maturation and to the presence of chemical detrimental compounds (as CGAs), with negative impact on the beverage quality (Vaast et al, 2006;Geromel et al, 2008;Bertrand et al, 2012;Barbosa et al, 2012). Furthermore, it is known that these environmental limitations of high temperature and chronic low water availability reported for this region will impact the plant at the physiological level, namely in what concerns the maintenance of balance between respiration and photosynthesis.…”
Section: Northeast Regionmentioning
confidence: 55%
“…Fatores do ambiente, como temperaturas anuais mais baixas recorrentes em maiores altitudes, associados a eventos fisiológicos, como períodos mais longos de enchimento dos grãos, são relatados na literatura e fornecem indícios para explicar as diferenças encontradas na composição química do grão, responsáveis pela qualidade final da bebida (FAGAN et al, 2011;GEROMEL et al, 2008;VAAST et al, 2006).…”
Section: Resultsunclassified
“…There was similar report from Jima zone of Ethiopia (Bote and Struik, 2011). Finding of Geromel et al (2008) indicated that coffee weight was significantly higher in shade zone. Earlier study of Muleta et al (2011) from southwest Ethiopia also confirm higher coffee yield from shade grown.…”
Section: Coffee Weightmentioning
confidence: 97%